INFLUENCE OF THE PERCEIVED TASTE INTENSITY OF CHEMESTHETIC STIMULI ON SWALLOWING PARAMETERS GIVEN AGE AND GENETIC TASTE DIFFERENCES IN HEALTHY ADULT WOMEN - Pelletier, Cathy A. (J Speech Lang Hear Res, 2014)
PURPOSE: This study examined whether the perceived taste intensity of liquids with chemesthetic properties influenced lingua-palatal pressures and submental surface electromyography (sEMG) in swallowing, compared to water. METHOD: Swallowing behaviors were studied in 80 healthy women, stratified by age-group and genetic taste-status. General Labeled Magnitude Scale ratings of taste intensity were collected for deionized water; carbonated water; 2.7 % w/v citric acid; and diluted ethanol. These stimuli were swallowed, with measurement of tongue-palate pressures and submental sEMG. Path analysis differentiated stimulus, genetic taste-status, age, and perceived taste intensity effects on swallowing. Signal amplitude during effortful saliva swallowing served as a covariate accounting for differences in participant strength. RESULTS: Significant differences in taste intensity were seen across liquids: citric acid > ethanol > carbonated water > water. Supertasters perceived greater taste intensity than nontasters. Lingua-palatal pressure and sEMG amplitudes were correlated with the strength covariate. Anterior palate pressures and sEMG amplitudes were significantly higher for the citric acid stimulus. Perceived taste intensity was a significant mediator of stimulus differences. CONCLUSIONS: These data support the idea that sensory input transmitted via chorda tympani and trigeminal afferent pathways may lead to cortical facilitation and/or modulation of swallowing.